Diagnostic and therapeutic considerations in biopsy‐proven type 2 autoimmune pancreatitis: comparative analysis with biopsy‐proven type 1 autoimmune pancreatitis. Issue 5 (28th December 2020) - Pattabathula, Krishna; Waters, Peadar S.; Hwang, Jason; Bettington, Mark; Singh, Mahendra; Bryant, Richard D.; Cavallucci, David J.; O'Rourke, Nicholas
Abstract: Background: Autoimmune processes are now an increasingly recognized cause of acute and chronic pancreatitis. Autoimmune pancreatitis is a rare, benign pathology with two distinct clinicopathologic subtypes. The aim of this study was to compare the presentation, diagnostic considerations and outcomes of patients with biopsy‐proven type 1 and 2 autoimmune pancreatitis (AIP). Methods: A retrospective review of the Queensland Health pathology database of histologically proven AIP was conducted. Parameters compared included demographics, diagnostic criterion and post‐treatment outcomes. Results: Twenty‐three patients had a confirmed histological diagnosis of AIP (type 1 = 13, type 2 = 10). Patients with type 2 AIP were younger (median age 49 versus 59 years, P  < 0.05). There was no significant difference in gender distribution of disease at presentation. Type 2 AIP presented with significant increased focal pancreatic changes on cross‐sectional imaging (80% versus 54%, P  < 0.05). Serum IgG4 levels were raised (>1.40 g/L) in 69% of patients with type 1 AIP and not detected in type 2 ( P  < 0.01). Concurrent underlying inflammatory bowel disease was present in a higher proportion of type 2 AIP (40% versus 15%, P  < 0.05). A significantly increased proportion of patients with type 2 AIP underwent surgical resection (70% versus 30%, P  < 0.05). Conservative management was utilized in more patients with type 1 disease (54% versus 30%). On follow‐up, two patients have experienced symptomatic relapse at 6–18 months. Conclusions: Diagnostic challenges do exist and clinicians must suspect 2 type AIP in young, serum IgG4‐negative inflammatory bowel disease patients with recurrent pancreatitis. Abstract : Diagnostic challenges do exist in type 2 autoimmune pancreatitis (AIP). Patients with type 2 AIP were significantly younger, with focal disease on cross‐sectional imaging, without elevation of igG4 levels, with concurrent inflammatory bowel disease and required more operative intervention. There was no significant difference observe in relapse rates and gender at presentation. Clinicians must suspect 2 type AIP in young, serum IgG4‐negative inflammatory bowel disease patients with recurrent pancreatitis.